2023
DOI: 10.1002/advs.202302301
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Engineering of 2D Materials‐Based Heterostructures for Electrochemical Energy Conversion

Yujia Zhang,
Kunkun Nie,
Lixin Yi
et al.

Abstract: Abstract2D materials, such as graphene, transition metal dichalcogenides, black phosphorus, layered double hydroxides, and MXene, have exhibited broad application prospects in electrochemical energy conversion due to their unique structures and electronic properties. Recently, the engineering of heterostructures based on 2D materials, including 2D/0D, 2D/1D, 2D/2D, and 2D/3D, has shown the potential to produce synergistic and heterointerface effects, overcoming the inherent restrictions of 2D materials and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 211 publications
(378 reference statements)
0
5
0
Order By: Relevance
“…In BS-2, 1D nanorods can provide efficient electron transport pathways, while 2D nanosheets or nanoplates can offer a high density of exposed catalytic active reaction sites. 64,65 Combining 1D and 2D structures may create synergistic effects that enhance the overall catalytic activity of BS-2.…”
Section: Resultsmentioning
confidence: 99%
“…In BS-2, 1D nanorods can provide efficient electron transport pathways, while 2D nanosheets or nanoplates can offer a high density of exposed catalytic active reaction sites. 64,65 Combining 1D and 2D structures may create synergistic effects that enhance the overall catalytic activity of BS-2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the particle size effect on the optical properties in THz wave region shows the importance of controlling particle size when developing new functional nanomaterials. [56][57][58][59] The present study showed that small particle size m-ZrO 2 has potential to be an absorber in THz wave technologies such as beyond 5G, advanced driver assistance systems (ADAS) and non-contact biological monitoring, in order to ensure stable operation with reduced noise. [60][61][62][63][64][65][66][67][68][69][70][71][72]…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the engineering of heterostructures based on 2D materials, has demonstrated the potential to induce synergistic effects, elevating the electrochemical energy conversion performance to new heights [122]. The stability of the heterostructures created between the charge transport layers and the perovskite films is critically important to the overall device's long-term viability, thus it attracted much attention.…”
Section: D/3d Phjmentioning
confidence: 99%